Murder one - Bernhardt, William, 1960- (New York: Ballantine Books, 2001)
The crime is remarkably heinous: veteran poliice detective Joe McNaughton is found savagely slain, mutilated, and hung from a public fountain in downtown Tulsa. The accused is a tabloid reporter's dream: stunning nineteen-year-old Keri Dalcanton, a stripper involved in a kinky affair with the married McNaughton. Crusading attorney Ben Kincaid takes up her defense. But when a police raid on his office uncovers the bloodstained murder weapon, Ben himself is charged with conspiracy and murder. What follows is a breathlessly twisting battle of legal wits--and lethal surprises--in which no holds are barred, no secrets are left unexposed, and ultimately, nothing is what it seems....
Includes excerpt from "Final round."
Keywords: Kincaid, Ben (Fictitious character); Tulsa (Okla.); Legal stories; Mystery fiction